System analysis and design of a thin client system for the University of the Philippines School of Library and Information Studies Library - Madriñan, Aaron Paul L.
Based on the recommendations of a previous study on the UP School of Library and Information Studies (SLIS) information systems, this paper sought to analyze and design a thin client system for the UP SLIS library. It intended to determine the economic feasibility of this particular information system as well as discover the benefits it can confer to the UP SLIS community. It also looked into the differences in functionality and the impressions of the users when compared to the current desktop systems in the SLIS library.